Hubungan Pengetahuan, Sikap, dan Paparan Youtube Terhadap Perilaku Merokok Elektrik pada Mahasiswa Universitas Pembangunan Nasional Veteran Jakarta - Harsaq, Nayla Zamzani; Aristi, Della; Nurullinisa, Wulan; Wulandari, Dewi Yully (Faculty of Health Sciences, Syarif Hidayatullah State Islamic University of Jakarta, 2025)
E-cigarettes are battery-powered devices that heat liquid to produce vapor. Their use is increasing among college students, especially due to exposure to social media such as YouTube. E-cigarettes can cause nicotine dependence and various diseases. This study aims to determine the relationship between knowledge, attitudes, and YouTube exposure to e-cigarette smoking behavior among UPN Veteran Jakarta students in 2024. We used cross-sectional design and accidental sampling technique, involving 160 respondents. Data analysis using the Chi-Square test. A total of 45.6% of respondents have e-cigarette smoking behavior. There is a significant relationship between knowledge, attitudes, and exposure to negative and positive content on YouTube with e-cigarette smoking behavior (p-value <0.05). The high number of students who smoke e-cigarettes is influenced by peer influence, perceptions of the safety of e-cigarettes, and exposure to content. Negative content encourages smoking behavior through advertising and promotions, while positive content increases awareness of the risks. Students' knowledge and attitudes are also significantly related to e-cigarette smoking behavior. Knowledge, attitude, exposure to negative content, and exposure to positive content have a significant relationship with e-cigarette smoking behavior. Students can be more active in seeking information from trusted sources about the dangers and risks of e-cigarettes. Campus regulations also can prohibit the use of e-cigarettes and other tobacco products on campus. As a step to reduce e-cigarette consumption, students can train themselves to manage stress and emotions healthily without relying on e-cigarettes by using relaxation techniques.